STRATEGI UPAYA PENGENTASAN KEMISKINAN MELALUI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DI JAWA TIMUR - Putri, Erni Puspanantasari (JHP17 (Jurnal Hasil Penelitian), 2016)
The purpose of this study were (1) Identify the factors that impede businessdevelopment of micro, small and medium enterprises in East Java, (2) identifystrategies flagship relevant for micro, small and medium enterprises in EastJava, (3) Develop a strategy formulation the development of micro, small andmedium enterprises in East Java as the alleviation of poverty. by using theSWOT method, it can be concluded that (1) the factors that impede businessdevelopment of micro, small and medium enterprises in East Java is the lowmarketing, promotion is still lacking, innovation competitor products quickly,the condition of the competitors are very strict, government policy to reducepublic subsidies, high inflation, weak niai rupiah against the $ US, demands aquality product at a price that is increasingly Competitive, the decline of thecountry's economy, political situation in the country is not stable, (2) Strategyflagship relevant to micro, small and medium enterprises in East Java Growthstrategy, showed no growth and product diversification efforts, micro, smalland medium enterprises, Stability strategy, shows the strategy adopted withoutchanging the strategic direction set. (3) The formulation of the developmentstrategy of micro, small and medium enterprises in East Java as the fightagainst poverty is (a) Creating opportunities for new markets, for example,Open gallery to accommodate everyone who wants to learn about batik,designs, colors and patterns are new , Producing cotton batik arise, fabricdoby, woven fabrics batik, fabric paris (semi ciffon), silk, production of herbalmedicine in the form of sachets, Forms / ways of marketing, micro, small andmedium enterprises : exhibitions, internet, stand at the site of micro, small, andintermediate, product marketing process: www. petismadura.com through online, by telephone, came to the site of micro, small and medium enterprises, (b)Measures craftsmen of micro, small and medium enterprises to facecompetition, for example, cotton batik patterned producing contemporarycraftsmen who work in Tanjungbumi invited back to the village in Sampang,designs, colors and patterns are new, it needs creative freedom batik, andaccording to standard batik, development capital, collecting batik former, Formedicinal products: produce products with packaging per ounce, for productpaste: improved quality, competitive prices, CSR for young, expanding theimage to the public, To handicraft: should innovation models, especially theproducts of bags and wallets, information from the Internet, (c) Effortscraftsmen that demand the products increases, for example, promotion of one toStrategi Upaya Pengentasan Kemiskinan Melalui Pengembangan Usaha Mikro Kecil dan MenengahDi Jawa Timur106the other, for batik products: create a new motive, the exhibition, plus employeeand machine, plus shops, for the product chips fish : without chemicals, forproducts skull cap: rent for wholesale, product diversification is koko, exhibits10 times in 1 year.Keywords: SWOT, micro small and medium enterprise, poverty alleviation